Pengaruh Volume Perdagangan Saham, Volatilitas Laba, Dividend Yield, dan Ukuran Perusahaan Pada Volatilitas Harga Saham - Andiani, Ni Wayan Sekar; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 24 No 3 (2018)DO - 10.24843/EJA.2018.v24.i03.p19, 2018)
This study aims to obtain empirical evidence on the effect of stock trading volume, earning volatility, dividend yield, and firm size on stock price volatility. This research was conducted on companies listed in index LQ 45 in Indonesia Stock Exchange 2012 until 2016. This research took the population of 45 companies with the number of samples of 21 companies selected through purposive sampling, so the number of samples observation for 5 years to 105 companies. The analysis technique in this research is multiple linear regression analysis. Based on the analysis results found that the stock trading volume does not affect the stock price volatility. Earning volatility has a negative effect on stock price volatility. This shows the higher volatility of profits owned by the company tends to reduce the interest of investors to invest or can reduce the volatility of stock prices. Dividend yield has a positive effect on stock price volatility. Which means that the higher dividend rate can affect the high investor interest to invest in the capital market, causing a stock price reaction. The firm size has a negative affects on stock price volatility. This proves the greater the size of the company indicates a stable corporate condition and able to reduce the volatility of stock prices. Keywords: Stock Trading Volume, Earning Volatility, Dividend Yield, Firm Size, Stock Price Volatility.